Synthesis of aminocyclitols. - Yu, Ruey-Jiin. (University of Ottawa (Canada), 1965)
Part I. The catalytic hydrogenation of 4,6-dinitropyrogallol was investigated under a variety of conditions. Whereas it proved difficult to hydrogenate the benzene ring with palladium catalysts, the use of platinum catalyst led to an uptake of nine moles of hydrogen as required for the production of diamino-trihydroxycyclohexanes. The hydrogenation products were isolated as solid hydrochlorides or sulfates in yields of 29--46%. They were shown by paper chromatography to be mixtures of several compounds. Ion exchange column chromatography resulted in the isolation, as crystalline dihydrochlorides, of five unknown aminocyclitols: three stereoisomeric diamino-trihydroxycyclohexanes and two stereoisomeric diamino-dihydroxycyclohexanes. The compounds were characterized by their chromatographic mobilities relative to 2-deoxystreptamine (R ds 0.74, 0.80, 0.96, 1.15, and 1.35), by elemental analyses, x-ray diagrams, and by the preparation of derivatives. Their structures and configurations followed from periodate oxidation and nuclear magnetic resonance studies. The following assignments were made. (1) Compound Rds 0.74: 1alpha,3alpha-diamino-4alpha,5alpha,6alpha,trihydroxycyclohexane (XV); (2) Compound Rds 0.80: D, L-1alpha,3alpha-diamino-4alpha,5alpha,6beta-trihydroxycyclohexane (XVI); (3) Compound Rds 0.96: D,L-1alpha,3beta-diamino-4alpha,5alpha,6alpha-trihydroxycyclohexane (XVII); (4) Compound Rds 1.15: 1alpha,3alpha-diamino-4alpha,6alpha-dihydroxycyclohexane (XVIII); (5) Compound Rds 1.35: D,L-1alpha,3alpha-diamino-4alpha,6beta-dihydroxycyclohexane (XIX). Part II. For a stereospecific synthesis of 2-deoxystreptamine (XI) the diketone XXVII, 4,5,6-xylo-trimethoxy-1,3-cyclohexanedione, was needed. It was attempted to synthesize this diketone in a number of ways. Reaction of 2,3,4-tri-O-methyl xylaryl chloride (XXXVI) and methylene dimagnesium diiodide or methylene cadmium did not yield the expected product. A Dieckmann type cyclization of dimethyl 2,3,4-tri-O-methyl-xylarate (XXXII) with methyl (or ethyl) acetate failed to produce the expected 4,5,6- xylo-trimethoxy-2-carboalkoxy-1,3-cyclohexanedione (XXXIX). Methyl hydrogen 2,3,4-tri-O-methyl-D,L-xylarate (XLI) was prepared from the corresponding diester XXXII by partial hydrolysis. The half ester XLI was converted to an acyl chloride, gamma-carbomethoxy-D,L-xylo -trimethoxybutyryl chloride (XLIII). This acyl chloride was reacted with diazomethane followed by hydriodic acid reduction of the diazoketone, in the expectation that methyl 6-deoxy-2,3,4-tri-O-methyl-D,L- xylo-5-hexulosonate (XL) (C10H18O6) be formed. However, the reaction product appeared to have the composition C12H20O9. Reaction of the acyl chloride XLIII and dimethyl cadmium gave a compound C10H20O6.
Keywords: Chemistry, Organic.